2023
DOI: 10.3390/cancers15225335
|View full text |Cite
|
Sign up to set email alerts
|

CD46–ADC Reduces the Engraftment of Multiple Myeloma Patient-Derived Xenografts

Michael J. VanWyngarden,
Zachary J. Walker,
Yang Su
et al.

Abstract: An antibody–drug conjugate (ADC) targeting CD46 conjugated to monomethyl auristatin has a potent anti-myeloma effect in cell lines in vitro and in vivo, and patient samples treated ex vivo. Here, we tested if CD46–ADC may have the potential to target MM-initiating cells (MM-ICs). CD46 expression was measured on primary MM cells with a stem-like phenotype. A patient-derived xenograft (PDX) model was implemented utilizing implanted fetal bone fragments to provide a humanized microenvironment. Engraftment was mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…However, the role of sCD46 forms in the development of cervical cancer, and its mechanism of action remains unknown. Currently, targeting CD46 as a therapeutic strategy in cancers has attracted increasing attention to overcome the poor therapeutic efficacy of conventional cancer treatments, including the inhibition of CD46 expression (11,(29)(30)(31), neutralizing (blocking) mAbs (30)(31)(32), anti-CD46 antibody−drug conjugates (CD46-ADCs) (21, [33][34][35][36], and oncolytic virotherapy (37-42). It has been demonstrated that targeted downregulation of CD46 expression by siRNA in vitro increases the sensitivity of cancer cells to CDC (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of sCD46 forms in the development of cervical cancer, and its mechanism of action remains unknown. Currently, targeting CD46 as a therapeutic strategy in cancers has attracted increasing attention to overcome the poor therapeutic efficacy of conventional cancer treatments, including the inhibition of CD46 expression (11,(29)(30)(31), neutralizing (blocking) mAbs (30)(31)(32), anti-CD46 antibody−drug conjugates (CD46-ADCs) (21, [33][34][35][36], and oncolytic virotherapy (37-42). It has been demonstrated that targeted downregulation of CD46 expression by siRNA in vitro increases the sensitivity of cancer cells to CDC (11).…”
Section: Discussionmentioning
confidence: 99%
“…Sherbenou et al (34) suggested that CD46-ADC has the potential to be an effective treatment for multiple myeloma (MM), especially in patients with a gain of chromosome 1q. The curative potential of CD46-ADC has been confirmed in a patient-derived xenograft (PDX) model (35). In addition, exploratory toxicology studies of CD46-ADC in nonhuman primates have demonstrated an acceptable safety profile (21).…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of sCD46 forms in the development of cervical cancer, and its mechanism of action remains unknown. Currently, targeting CD46 as a therapeutic strategy in cancers has attracted increasing attention to overcome the poor therapeutic efficacy of conventional cancer treatments, including the inhibition of CD46 expression (11,(29)(30)(31), neutralizing (blocking) mAbs (30)(31)(32), anti-CD46 antibody−drug conjugates (CD46-ADCs) (21, [33][34][35][36], and oncolytic virotherapy (37-42). It has been demonstrated that targeted downregulation of CD46 expression by siRNA in vitro increases the sensitivity of cancer cells to CDC (11).…”
Section: Discussionmentioning
confidence: 99%
“…Sherbenou et al (34) suggested that CD46-ADC has the potential to be an effective treatment for multiple myeloma (MM), especially in patients with a gain of chromosome 1q. The curative potential of CD46-ADC has been confirmed in a patient-derived xenograft (PDX) model (35). In addition, exploratory toxicology studies of CD46-ADC in nonhuman primates have demonstrated an acceptable safety profile (21).…”
Section: Discussionmentioning
confidence: 99%